#TITLE_ALTERNATIVE# - (NIM 31193002), SANJAYA
Wood is considered as one of the materials widely used in daily life. Nowadays, it becomes more difficult to obtain high quality wood. This matter causes an increase of the use of low quality wood, which has a low dimension stability, so that it can expand and shrink in an environment of high humidity. Acetylation and formaldehydation are methods known to improve wood dimension stability. In the acetylation process, nucleophilic substitution of an oxygen atom (0) from a hydroxyl (-OH) group of wood components toward a carbonyl C atom from (CH3CO)20 occur, so that an -OH group of wood components is changed into an acetyl group, -OCOCH3. In the formaldehydation process, substitution of an -OH group of wood components with formaldehyde, HCHO occur forming a hemiacetal, R-OCH2OH or forming an acetal, R-OCH2-O-R with wood components. Based upon the macroscopic difference in wood structure, low quality wood consists of two groups, i.e. wide leaves wood and needle-like leaves wood. Wide leaves wood has a variable and complicated anatomic structure than needle-like leaves wood. The difference of the influence of acetylation and formaldehydation towards the molecular structure of wide leaves and needle-like leaves wood are not yet known. This matter is the main concern of this research. Wide leaves and needle like leaves wood are represented by Shorea leprosula Miq. and Pinus merkusii Jungh. et de Vr., respectively. Acetylation and formaldehydation are carried out at optimum condition, temperature, concentration and reaction time which gives the highest dimension stability if wood is immersed in water with a minimum change of appearance of wood. The optimum condition of acetylation is temperature 110oC, concentration (CH3CO)20 15 % in xylene, and reaction time 24 hour. The optimum condition of formaldehydation is temperature 100oC, concentration HCHO 10 % in acetic acid with HCl 5 % as catalyst, and reaction time 2 hour. The addition procedure has been modified from the general procedure, i.e diffusion of the additive solution into wood has been carried out at low pressures, about 12 cmHg to enhance the diffusion of additive solution into wood. Research data showed that additive penetration occurs quicker in needle-like leaves wood than in wide leaves wood. This is because wide leaves wood is complicated anatomic structure than needle like leaves wood. Anti swelling efficiency (ASE) results showed a higher increase of wood dimension stability of needle-like leaves wood than wide-leaves wood after addition. This shows that addition at needle-like leaves wood is more effective than addition at wide-leaves wood. The increase in dimension stability with formaldehyde is higher than with acetic-anhydride. This is because the formaldehyde molecule is smaller than acetic-anhydride one, so that formaldehyde diffuses and reacts easier with wood. Besides physical structure change, addition also causes a change in chemical structure of wood. Fourier Transform Infrared (FTIR) analyses shows that addition causes a change of the -OH group. Formaldehydation causes a bigger change of -OH group than acetylation. X-Ray Diffraction (XRD) analyses shows that addition decreases the crystalline structure of wood and cellulose. A crystalline structure is formed due to the regularity of cellulose polymer chains. With the entrance of additive, part of the hydrogen bond formed between the cellulose chains are broken, so that the amorphous region increases. The decrease in crystallinity of needle-like leaves wood is greater than in wide leaves wood. FTIR, XRD, photomacroscopy and photomicroscopy analyses of wood reveal that formaldehydation changes the wood structure more than acetylation. This is because in formaldehydation more -OH groups can be exchanged, so that the crystalline structure decreases. The lower crystallinity of wood, the more new spots are available for hydrogen bond formation. Differential Scanning Calorimetry (DSC) analyses shows that the amount of bound water is greater after additive treatment of wood. Formaldehydated wood binds more H2O than acetylated wood. FTIR, XRD and DSC analyses revealed the role of the main chemical components of wood in obtaining dimension stability of wood. Cellulose performs better in formaldehydation than acetylation, while lignin performs better in acetylation than in formaldehydation. In Formaldehydation of cellulose, the substitution reaction of -OH group better than acetylation. As a conclusion the acetylation and formaldehydation of wood may increase the dimension stability of wood due to the change in wood molecular structure. The change in wood molecular structure has been identified by the partial change of -OH groups by a greater groups which causes an increase of the amorphous region. The increase of amorphous region causes an increase in the ability of wood to adsorb water, which also means the possibility of expansion of wood. However, since the new functional group is greater than the -OH group, it will cause a steric hindrance towards the ease of movement of wood molecules. Due to this restricted movement, the possibility of volume expansion of wood decreases, or in other words the wood dimension stability increases.